Shared action on food and environments in East Africa - Vervoort, Joost M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
What does the future hold for food security and adaptation to climate change in East Africa? What if there was concerted action towards political and economic integration? What if the opposite happened, and the region became even more fragmented, with people in power focusing on their own narrow gains? The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) has explored how different political and socio-economic futures for East Africa may affect food security and environmental change in the region, and how this may affect the region’s vulnerability to future climate change. This briefing presents four possible scenarios and the insights gained during the process of developing them. It describes how stakeholders have used them to plan for the future, and explores emerging policy options.